Key factors and readiness perception indicators appraisal: Public-Private partnership in infrastructure development project in Bangladesh - Islam, Md. Rezaul (BRAC University, 2014)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2012.